PEMBERIAN ADOK MASYARAKAT KOMERING DI OKU TIMUR (KAJIAN TRADISI LISAN) - Ratu Wardarita; Achmad Wahidy; Yessi Fitriani (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2022)
This study describes meaning, function, cultural, religious and social values in the giving of adok in Komering community in East Ogan Komering Ulu (OKU) Regency, South Sumatra which is considered as a real manifestation of local wisdom. This study uses a qualitative descriptive method in which data collection techniques of observation, interviews, recording, note taking, and translation are integrated. The results of the study describe that giving adok contains elements of pisaan, adok, and warahan which has the meaning of prayer, hopes and ideals of greatness and glory must be carried out by the Adok holder. In addition, the elements of Pisaan, Adok and Warahan in giving Adok can also be utilized as controls in behaving in social status, and also as moral value and transmitter from the ancestors to their generators in order to be maintained and preserved. Cultural values in the adok tradition include cultural values in human relations with God in the form of faith and obedience to the Creator; cultural values in human relations with other humans such as: kind, not forgetting parents; cultural values in human relations with oneself, such as: be patient and always grateful, and not sitting idle; Cultural values in human relations with nature are like betel leaf and thick leaves for medicine. Religious and social values in the adok process describe the behavior of human life which must reflect deep holistic and aesthetics and be implemented in every aspect of life of the Adok holder.Penelitian ini mendeskripsikan makna, fungsi, nilai budaya, nilai agama dan nilai sosial adok pada masyarakat Komering di Kabupaten Ogan Komering Ulu (OKU) Timur, Sumatera Selatan sebagai wujud nyata kearifan lokal. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, perekaman, pencatatan, dan penerjemahan. Hasil penelitian mendeskripsikan bahwa pemberian adok mengandung unsur pisaan, adok, dan warahan yang memiliki makna doa, harapan, cita-cita, kebesaran, dan kemuliaan yang harus dilaksanakan oleh pemegang adok (gelar). Selain itu, unsur pisaan, adok dan warahan dalam pemberian adok berfungsi juga sebagai kontrol dalam bertindak dan penanda kedudukan sosial dalam masyarakat serta penyampai pesan moral para leluhur kepada penerusnya agar dapat terus dijaga dan dilestarikan. Nilai budaya pada tradisi adok meliputi nilai budaya dalam hubungan manusia dengan Tuhan berupa keimanan dan ketaatan kepada sang Pencipta; nilai budaya dalam hubungan manusia dengan manusia lain, misalnya baik hati, tidak melupakan orang tua; nilai budaya dalam hubungan manusia dengan diri sendiri, misalnya sabar, selalu syukur, serta tidak berpangku tangan; nilai budaya dalam hubungan manusia dengan alam, misalnya daun sirih dan daun lebat untuk obat. Nilai agama dan nilai sosial dalam proses adok mendeksripsikan perilaku kehidupan manusia yang harus mencerminkan etika dan estika secara mendalam dan dapat diimplementasikan dalam setiap sendi kehidupan pemegang adok.